2019
DOI: 10.1039/c8cy01139g
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the mechanism of the UiO-66-catalyzed sulfide oxidation: activity and selectivity enhancements through changes in the node coordination environment and solvent

Abstract: “Open” sites on the nodes of UiO-66 are converted to catalytically active Zr-OOH and can coordinate with solvent/products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 66 publications
0
48
0
Order By: Relevance
“…Finally, we tried to analyze a possible role of defects in the Zr‐MOF structures in the H 2 O 2 ‐based catalytic oxidations. Previously, two groups concluded that defects play a significant role in the thioether oxidation over UiO‐66 [6c, 7b] . TGA measurements showed that the concentration of defects corresponding to the total amount of terminal Zr(OH/H 2 O) groups decreased in the order Zr‐abtc > MIP‐200 > UiO‐67 > UiO‐66 (Table S2, Figures S8–S12 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Finally, we tried to analyze a possible role of defects in the Zr‐MOF structures in the H 2 O 2 ‐based catalytic oxidations. Previously, two groups concluded that defects play a significant role in the thioether oxidation over UiO‐66 [6c, 7b] . TGA measurements showed that the concentration of defects corresponding to the total amount of terminal Zr(OH/H 2 O) groups decreased in the order Zr‐abtc > MIP‐200 > UiO‐67 > UiO‐66 (Table S2, Figures S8–S12 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 94%
“…Zr‐MOFs constructed from the highly robust Zr 6 O n (OH) m clusters and various carboxylate linkers are one of the most attractive classes of MOFs owing to their outstanding thermal, hydrothermal, chemical, and mechanical stability as well as a tunable amount of defects [5] . In particular, the most studied representative of Zr‐MOFs, Zr IV terephthalate UiO‐66, has been employed as a leaching‐tolerant and recyclable catalyst for a range of H 2 O 2 ‐based oxidative transformations, [6, 7] the majority of which were oxidations of S compounds [6a–c, 7b] …”
Section: Introductionmentioning
confidence: 99%
“…Such “open” sites are much more coordinatively labile than the chelating carboxylate‐capped sites obtained with acid modulators and can become active sites in catalysis. A combined experimental and computational study shows that monocarboxylate‐capped missing‐linker defects on the Zr 6 ‐oxo‐hydroxo node of UiO‐66 MOFs can be converted into unsaturated coordination sites that serve as good catalysts . However, it cannot be neglected that less crystalline materials suffer from both lower chemical and mechanical stability …”
Section: Mof Catalysts For Odsmentioning
confidence: 99%
“…The stability of UiO-66 structure explains its wide use in heterogeneous catalysis. It was studied, e.g., in transesterification of triglyceride with methanol [24], sulphide oxidation [25], desulfurization [26], and other reactions [27]. A number of papers concerning catalytic performance of the UiO-66 modified in Zr nodes or the BDC linker, or decorated with metals, was published.…”
Section: Introductionmentioning
confidence: 99%